Insight. Upper-Intermediate: workbook - Roberts R. Rachael (Oxford Exam Support)
The insight Workbook is an essential accompaniment to the Student's Book, providing further practice for your students, plus an abundance of extra resources including Literature insight, Pronunciation insight and Exam insight sections.